VCAR: Vedic Compression Algorithm over Region of interest on radiological image - Suma; Sridhar, V. (2015 International Conference on Emerging Research in Electronics, Computer Science and Technology (ICERECT), 2015)
Performing an effective, reliable, and faster compression is one of the important processes in managing the radiological images that relates to either storage or transmission purpose. Ensuring no loss of significant clinical information during transmission along with faster computational capabilities are quite less to find in literature pertaining to medical image compression techniques. Therefore, this paper introduces a technique called as VCAR or Vedic Compression Algorithm over Region of interest that uses the potential vertical and cross over multiple characteristics of Urdhava Tiryakbhyam sutra in Vedic mathematics. VCAR takes the input image as region of interest extracted by author's prior technique and then subjects it to compression. The outcome of the study was found to be superior compared to frequently used DCT-based compression techniques with respect to computational speed, Peak Signal to Noise Ratio (PSNR), visual quality in the forms of bits per pixels over multiple standard medical image databases.